2013
DOI: 10.3109/02770903.2013.845205
|View full text |Cite
|
Sign up to set email alerts
|

A review of barriers to effective asthma management in Puerto Ricans: cultural, healthcare system and pharmacogenomic issues

Abstract: We believe that culturally sensitive community-based asthma education programs can serve as models for programs targeted toward Puerto Ricans to help decrease asthma morbidity. Moreover, greater sensitivity to Puerto Rican mores and folk remedies on the part of healthcare providers may improve the patient-clinician rapport and, hence, asthma outcomes. Finally, given ethnically based differences in pharmacogenomics, clinical trials targeting the Puerto Rican population may help to better define optimal asthma m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Latino groups in the United States of America). People from these groups have also been shown to have poorer asthma outcomes La Roche 2006;Alicea-Alvarez 2014). Furthermore, there is a growing body of literature highlighting the need to tailor asthma education programs specifically for ethnic and cultural groups to improve asthma outcomes (Poureslami 2012; Press 2012; Douglas 2013; Stewart 2013; Alicea-Alvarez 2014; Speck 2014; National Asthma Council Australia 2015; BTS 2016).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Latino groups in the United States of America). People from these groups have also been shown to have poorer asthma outcomes La Roche 2006;Alicea-Alvarez 2014). Furthermore, there is a growing body of literature highlighting the need to tailor asthma education programs specifically for ethnic and cultural groups to improve asthma outcomes (Poureslami 2012; Press 2012; Douglas 2013; Stewart 2013; Alicea-Alvarez 2014; Speck 2014; National Asthma Council Australia 2015; BTS 2016).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Research has identified that parental belief systems, culture, language and socioeconomic forces are factors that contribute to poor medication adherence for Latino children [7]. In place of prescription medications, caregivers often turn to folk remedies, rubs, herbal treatments, spirituality and behavioral strategies or modifications to treat their child's asthma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cultural barriers, which include language, are one of the main causes of disparities in health care, as providers who lack cultural sensitivity and competence carry a set of cultural beliefs which may be at odds with that of their patients. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Cultural barriers, which include language, are one of the main causes of disparities in health care, as providers who lack cultural sensitivity and competence carry a set of cultural beliefs which may be at odds with that of their patients. 6,7 Hispanics are often more dissatisfied than non-Hispanics with the care received and communications with their health care providers. [7][8][9][10] In 1999, Morales et al 8 investigated the possible association of ethnicity and language with communication satisfaction by surveying a sample of Hispanic and White patients on their contentment with medical staff listening skills, provision of answers and explanations, and reassurance and support (Table 1).…”
Section: Introductionmentioning
confidence: 99%